Analisis Minat Mahasiswa Pendidikan Bisnis UPI dalam Penggunaan Aplikasi Trading Saham Berbasis Syariah - Muhamad Parhan; Fariel Vernain; Wulan Gustiani; Shifa Syalsa Agistina (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Achmad Yani Yogyakarta, 2025)
Students will find it easy to get information about regarding sharia-based stock trading. By investing in sharia, students gain profits without fear of usury. The purpose of this research is to determine the interest of students of the Indonesian Education University Business Education in using sharia-based stock trading applications or websites. This research uses qualitative methods by conducting interviews with several 3rd semester students Business Education. This research uses data from 3 respondents woman. Based on the research results, the Business Study interest in using sharia-based stock trading applications or websites, meaning there was very high student interest in using sharia-based stock trading applications or websites. Respondents said it was important. 2 respondents did not do stock trading, 1 respondent used stock trading conventional. The research results show that there are very few UPI Business Education who use stock trading, but they have a high interest in using stock trading.